Behavioural and molecular effects induced by Cannabidiol in animal models of depression - Silote, Gabriela Pandini (2021)
Introduction: Major depressive disorder (MDD) is a chronic and severe psychiatric disorder, which is more prevalent in women. Cannabidiol (CBD) is a compound isolated from the plant Cannabis sativa L., which produces an antidepressant-like effect in animal models. However, only a few studies investigated the effect of such compounds in females, and it is unclear the influence of gender on CBD effects. The antidepressant effect induced by CBD involves the activation of BDNF-TrkB-mTOR signaling in the hippocampus and prefrontal cortex, an effect also demonstrated for ketamine. Aims: The present study aimed to: investigate the influence of strain and gender of mice in CBD antidepressant-like effects (Study 1A); investigate CBD effects in male and female FSL rats, tested at different time points (Study 1B); investigate the molecular mechanisms involved in CBD and ketamine antidepressant effect in the prefrontal cortex (PFC) and hippocampus of FSL rats (Study 2). Methods: Study 1: Adult male and female Swiss and C57BL/6 mice and adult male and female FSL and Flinders Resistant Line (FRL) rats were used. Mice received the systemic injection with CBD (3, 10, and 30 mg/kg, i.p.), imipramine (IMIP; 20 mg/kg, i.p.) or vehicle 30 minutes before the elevated plus maze (EPM) and tail suspension test (TST). FSL rats were treated with CBD (10, 30, and 60 mg/kg, i.p.), S-ketamine (15 mg/kg, i.p.) or vehicle, 1 or 2 hours before the open field test (OFT) and forced swim test (FST). An independent experiment was conducted with female FSL rats that received S-ketamine (10, 15, and 20 mg/kg, i.p.) or vehicle 1h before OFT and FST to select ketamine effective dose. Study 2: Adult male FSL and FRL rats received intraperitoneal treatment with CBD (30 mg /kg), S-Ketamine (15 mg/kg) or vehicle (Saline and Tween 80 3%), 1h before behavioral tests in the OFT (5 min) and FST (5 min). Immediately after the behavioral tests, the PFC, dorsal hippocampus (DH), and ventral (VH) were dissected. To investigate the molecular mechanisms involved in the antidepressant-type effect induced by CBD and S-Ketamine, the analysis of gene expression (Fluidigm) and synaptosome protein levels by WB were performed on PFC, DH, and VH for the glutamatergic, neurotrophic signaling and synaptic plasticity. Results: Study 1A: CBD produced an antidepressant-like effect in male, but not in female Swiss mice in the TST. Furthermore, CBD did not induce any significant effect in C57BL/6 mice, both males and females. Study 1B: Surprisingly, in FSL rats, CBD (30 mg/kg) induced a depressive-like effect in females 1 hour after the treatment, but an antidepressant-like effect after 2 hours. In males, CBD (30 mg/kg) produced an antidepressant-like effect 1 hour after the injection; no effect could be observed following 2 hours. Ketamine induced a significant antidepressantlike effect in female FSL rats submitted to FST 1 hour after the injection (15 and 20 mg/kg). Study 2: We replicated the behavioural results from Study 1B, the injection of CBD and ketamine reduced the immobility time in FSL rats exposed to FST, which reinforces our findings. There was no correlation between the CBD blood levels and the immobility exhibited in the FST. In the molecular analysis, the effect of CBD was associated with increased expression of the EAAT3, Nr2a, Nr2b, BDNF transcript in the PFC. In contrast, ketamine effect was associated with downregulation in VEGF and sortilin levels and increased protein levels of Nr2b, Nr2a and pGluR1 (S831) in the same region. However, in DH, CBD increased the levels of VEGF and Nr2b and decreased the expression of Sort1 and pGluR1 (S831), and ketamine reduced the expression of pGluR1 (S831) and increased the levels of Nr2b protein. In VH, CBD reduced the expression of mGluR5 and pGluR1 (S831 and S845) and increased the expression of GluR2, and ketamine reduced the levels of pGluR1 (S831) in the same limbic region. Conclusion: Based on the present findings, we conclude that CBD effects can be influenced by species, strain, gender, and time of administration. The molecular mechanisms involved on CBD antidepressant-like effect involves the regulation of the neurotrophic and glutamatergic signaling pathway in the PFC, DH and VH. In contrast, the effect of ketamine seems to involve mainly the restoration of normal glutamatergic function in the limbic brain areas.